Silicon Nanocrystals 2010
DOI: 10.1002/9783527629954.ch5
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Properties and Heat Transport in Silicon‐Based Nanostructures

Abstract: IntroductionFor the past 40 years, crystalline Si (c-Si) continues to be the major material for microelectronics, and modern silicon technology is superior compared to other semiconductors (e.g., II-VI and III-V compounds). In addition to the unique electronic and structural properties of bulk c-Si, silicon dioxide (SiO 2 ) and Si/SiO 2 interfaces, single-crystal Si possesses one of the best known lattice thermal conductivity [1,2]. This exceptional heat conductance is critically important for Si device heat m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 176 publications
(230 reference statements)
0
3
0
Order By: Relevance
“…On considering the Raman measurements, we anticipate that under the applied laser excitation intensity of 10 2 -10 3 W/cm 2 the sample temperature increases, and such temperature increase can be detected by monitoring the Raman peak wavenumber and FWHM temperature dependencies (44)(45)(46). Generally, as temperature increases the Raman ECS Transactions, 98 (2) 13-28 (2020) peak shifts toward lower wavenumber due to thermal expansion and changes in the selfenergy of the vibrational mode.…”
Section: Discussionmentioning
confidence: 99%
“…On considering the Raman measurements, we anticipate that under the applied laser excitation intensity of 10 2 -10 3 W/cm 2 the sample temperature increases, and such temperature increase can be detected by monitoring the Raman peak wavenumber and FWHM temperature dependencies (44)(45)(46). Generally, as temperature increases the Raman ECS Transactions, 98 (2) 13-28 (2020) peak shifts toward lower wavenumber due to thermal expansion and changes in the selfenergy of the vibrational mode.…”
Section: Discussionmentioning
confidence: 99%
“…In Si/SiGe CMs, we typically find that the volume fraction of SiGe is nearly twice that of Si/SiGe SLs, and it has been noted that inelastic scattering of phonons in Si/SiGe nanostructures with a diffuse interface also contributes to the reduction in the thermal conductivity (31). It was also reported that the temperature calculated according to Boltzmann statistics under a non-resonant excitation condition of the Ge-Ge phonon mode is consistently lower than that found for the Si-Ge and Si-Si modes (30). This discrepancy can be explained assuming that at the laser excitation wavelengths used, the Ge-Ge phonon mode has a resonant component, as pointed out in References 12, 32, and 33.…”
Section: Raman Studies Of Thermal Conductivity and Heat Dissipation I...mentioning
confidence: 98%
“…Typically, Raman scattering measurements are performed using an intense laser beam. While c-Si and c-Ge have a high thermal conductivity (κ ≈ 100 Wm -1 K -1 ), in compositionally disordered SiGe alloys and Si/SiGe nanostructures κ ≤ 10 W m -1 K -1 (30). Thus, a significant temperature increase of a sample might occur during Raman scattering measurements and it will affect the Raman peak position, width, and line shape.…”
Section: Raman Studies Of Thermal Conductivity and Heat Dissipation I...mentioning
confidence: 99%